Maximum triceratops - Bakker, Robert T. (New York : Random House, 2004)
Introduces the very rare--and controversial--Triceratops Maximus, an aggressive, herbivorous dinosaur capable of driving off even a Tyrannosaurus Rex.
Accelerated Reader AR
Keywords: Triceratops -- Juvenile literature; Dinosaurs -- Juvenile literature